Exploitation of puddles for breakthroughs in claustrum research - Johnson, John-Irwin; Fenske, Brian A.; Jaswa, Amar S.; Morris, John A. (Frontiers in Systems Neuroscience, 2014)
Since its first identification as a thin strip of gray matter enclosed between stretches of neighboring fiber bundles, the claustrum has been considered impossible to study by many modern techniques that need a certain roominess of tissue for their application. Known as the front wall, vormauren in German from 1822, and still called avant-mur in French, we here propose a means for breaking into and through this wall, by utilizing the instances where the claustral tissue itself has broken free into more spacious dimensions. This has occurred several times in the evolution of modern mammals, and all that needs be done is to exploit these natural expansions in order to take advantage of a great panoply of technological advances now at our disposal. So here we review the kinds of breakout “puddles” that await productive exploitation, to bring our knowledge of structure and function up to the level enjoyed for other more accessible regions of the brain.